The effects of STEM-PBL mathematics module on secondary vocational students’ mathematical problem-solving skills / He Xue Ting and Norulhuda Ismail - Ting, He Xue; Ismail, Norulhuda (2023)
Against the background of the transformation from "Made in China" to "Created in China" and from a large country to a strong one in terms of human resources, vocational education has been given a new historical mission and social responsibility. High-quality skilled personnel with problem-solving ability has become the goal of secondary vocational education. However, the mathematical problem-solving ability of Chinese secondary students is very weak. Therefore, secondary mathematics education shoulders the mission of cultivating high-quality skilled talents with mathematical problem-solving ability. This study aimed to determine the effects of STEMbased education modules and project-based learning on students' mathematical problem-solving ability. In addition, to find out how students perceive the Mathematics STEM-PBL module. This study used a quasi-experimental design as a research methodology to explore STEM-PBL teaching modules. Two classes were selected in a secondary vocational school in Sichuan Province, China. One was a control class, and the other was an experimental class with 35 students in each class. While the control class adopted conventional strategy, the experimental class made use of the STEM-PBL module. Students' attitudes towards STEM-PBL were evaluated using semi-structured interviews, and their aptitude for solving mathematical problems was evaluated by a maths test. It was discovered that the STEM-PBL mathematics module may enhance students' aptitude for solving mathematical puzzles, and the majority of secondary students had favourable views towards the STEM-PBL mathematics module's instruction. The STEM-PBL module appears to be a promising teaching tool for enhancing mathematical problem-solving abilities, according to these data. The findings of this study will outline future research in STEM education and PBL practise and show how the STEM-PBL teaching module can enhance students' ability to solve mathematical problems.